Relations of the Republic of Armenia with the Entente States and the United States of America (February 1919-January 1920) - Petrosyan, Gegham (YSU Journal of International Affairs, 2024)
The article comprehensively presents and summarizes the main reasons why the Republic of Armenia at the first stage of its existence (June-November 1918) could not pursue an independent and free foreign policy and establish diplomatic relations with the Entente states and states loyal to the alliance.            In the new favorable geopolitical situation created by the final defeat of Ottoman Turkey and its allies in the First World War, the Republic of Armenia could already freely manage its foreign policy, and it was necessary to make efforts to establish more active diplomatic relations with the Entente states - the United States of America, France and England. It was also more than vital to establish relations with Soviet and non-Soviet (anti-Bolshevik) state entities of Russia and others that were important to us from a security point of view.            The article analyzes one of the priority issues for the Republic of Armenia in the new foreign policy realities - establishing relations with the United States of America. Political, diplomatic and technical difficulties and obstacles to establishing these relations have been identified and shown.
Keywords: Republic of Armenia; Entente states; USA; France; England; Soviet and non-Soviet (anti-Bolshevik) state formations of Russia; Ottoman Turkey; Georgia; Azerbaijan